Comparing Outcomes Following Salvage Microsurgery in Vestibular Schwannoma Patients Failing Gamma-knife Radiosurgery or Microsurgery. Issue 9 (October 2017) - Lee, Hyun-Jin; Kim, Mi Joo; Koh, Seung Hyun; Chang, Won Seok; Moon, In Seok
Abstract : Objective: The increasing use of primary gamma-knife radiosurgery (GKS) for the treatment of vestibular schwannoma (VS) has led to a concomitant increase in the number of patients requiring salvage surgery for GKS failure. When patients underwent GKS as the primary treatment, it is known that dissecting tumor from adjacent nerves during salvage surgery is more difficult. In this report, we share our clinical experience with such patients and analyze the clinical findings of patients with tumor regrowth/recurrence. Study Design: Retrospective chart review. Setting: Tertiary center. Patients: Nine patients who underwent salvage surgery for VS regrowth/recurrence after GKS or microsurgery were enrolled. Main Outcome Measures: Symptom progression, radiological changes, intraoperative findings, and surgical outcomes were evaluated and compared. Results: Six patients with previous GKS and three with previous microsurgery underwent salvage microsurgery. The most obvious symptom of tumor regrowth was aggravation of hearing loss. Salvage surgery in all patients was limited to subtotal or near-total resection via a translabyrinthine/transotic approach. Severe adhesion, thickening, and fibrosis were more prominent findings in the GKS than in the previous microsurgery group. Dissection of the tumor from the facial nerve was more difficult in the GKS than in the microsurgery patients. Despite anatomical preservation of the facial nerve in all the six patients, three in the GKS group, but none in the revision microsurgery group, had worsening of facial nerve function. Conclusion: Salvage microsurgery of VS after failed GKS is more difficult than revision microsurgery, and the facial nerve outcomes are relatively poor. Therefore, the primary method of VS treatment should be carefully chosen. Additional imaging studies are recommended in patients with a sudden change in hearing loss who underwent GKS.